Experimental Study of Cold-Formed Steel Bridge Girder in Various Shapes Under Static Loads - Allami, Ali; Hussain, Haleem K.; Majeed, Fareed H. (Civil Engineering Journal, 2026)
To facilitate accelerated bridge construction and reduce the cost of bridge design and construction, a cold-formed steel composite bridge girder has been suggested recently as an economical alternative. The new technology for the composite bridge girder includes a cold-formed steel plate and either a precast or cast-in-place reinforced concrete (RC) slab. Previous research on cold-formed steel concrete composite girders has introduced two new shapes for short-span bridge girders: a cold-formed steel tub girder and a folded plate girder system. No study has been conducted on the impact of shape on the static structural behavior of cold-formed composite girders for short-span bridges. This paper investigated the behavior of the cold-formed steel composite girders with different shapes in terms of ductility, stiffness, the ultimate failure load, crack resistance, and interfacial slip. Four shapes were carried out in this research: tub, open-box, and double C with and without lips. Six simply supported girder specimens were designed, fabricated, and subjected to static load tests. The results showed that the cold-formed steel double C lipped girder increased the ultimate load by 12.12% compared to the cold-formed steel tub girder. Additionally, the initial stiffness of the cold-formed steel double C girder increased by 21% compared to the cold-formed steel tub girder. The open-box shape specimen can effectively improve the cracking resistance of cold-formed steel composite girders compared to the cold-formed steel tub girders.